Country of Origin Effects and Design Product on Purchase Intention: How South Korean Skincare Become the Main Choice of Consumers? - Herrin, Debby Chintia; Adriansyah, Muhammad Ali; Rahmah, Dian Dwi Nur (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
This study aims to determine of the effect of country of origin and product design on purchase intention of South Korea skincare product. This study is using a quantitative approach This subject of this study was 110 consumers of South Korea skincare in X city which were selected using purposive sampling technique. Data collection method used are purchase intention scale, country of origin scale and design product scale. The data analysis technique uses multiple regression statistical tests. The results of the full model study show that there is an influence between country and origin and design product on purchase intention, namely the calculated F value = 5.074 > F table = 3.08, and p = 0.008 < 0.050. On the results of the gradual model regression test, it was found that there was a significant effect between country of origin and purchase intention, namely the value t count = -0.231 > t table = 1.982, and p = 0.014 < 0.050. Then in the design product with purchase intention, it shows that there is a significant effect with the value t count = 2.261 > t table = 1.982, and p = 0.026 < 0.050.Penelitian ini bertujuan untuk mengetahui pengaruh citra negara asal dan desain produk terhadap minat beli produk perawatan kulit dari Korea Selatan. Penelitian ini menggunakan pendekatan kuantitatif. Subjek dalam penelitian ini sebanyak 110 konsumen produk perawatan kulit dari Korea Selatan di Kota Samarinda yang dipilih menggunakan teknik purposive sampling. Alat ukur yang digunakan dalam penelitian ini menggunakan skala minat beli, citra negara asal, dan desain produk. Teknik analisa data menggunakan uji statistik regresi model berganda. Hasil penelitian model penuh menunjukkan terdapat pengaruh antara citra negara asal dan desain produk terhadap minat beli yaitu dengan nilai F hitung = 5.074 > F tabel = 3.08 dan p = 0.008 < 0.050. Pada hasil uji regresi model bertahap didapatkan adanya pengaruh signifikan antara citra negara asal dengan minat beli yaitu nilai t hitung = -2.486 > t tabel = 1.982, dan p = 0.014 < 0.050. Kemudian pada desain produk dengan minat beli menunjukkan terdapat pengaruh signifikan didapatkan nilai t hitung = 2.261 > t tabel = 1.982, dan p = 0.026 < 0.050.